Upaya meningkatkan kemampuan berpikir kreatif siswa dalam pembelajaran matematika melalui pembelajaran game based learning (GBL) pada kelas VII MTSN 2 Malang - mita, sheyla (Maliki Interdisciplinary Journal, 2025)
The purpose of this scientific study is to improve students’ creative thinking skills in mathematics learning through the application of the Game-Based Learning (GBL) model using expression puzzle game media in class VII MTsN 2 Malang. The method used in this study is Classroom Action Research (CAR) which is implemented in two cycles, namely Cycle I and Cycle II. Each cycle consists of four stages: planning, action implementation, observation, and reflection. The subjects in this study involved 30 students from class VII. The instruments used included a thinking creativity test, student activity observation sheets, student response questionnaires, and learning documentation. This study showed a significant increase in students’ creative thinking skills, which was seen from the average value before the action of 62.5 increasing to 71.2 in Cycle I, and reaching 81.4 in Cycle II, with a total increase of about 30%. Students’ responses to GBL learning were very positive, where 82% said they felt more motivated and 78% felt that learning became more enjoyable. The use of expression puzzles not only encourages active student engagement but also inspires them to think in original, flexible, and innovative ways. The rule that requires losing students to work on additional problems from PowerPoint proved to be an effective strategy in deepening understanding of mathematical concepts. Thus, it can be concluded that game-based learning using expression puzzles is an effective approach in enhancing students’ creative thinking skills and creating an interactive and meaningful learning environment.